Orchestrating A/P and D/V guidance - A Wnt/Netrin tale. Issue 1 (2nd January 2016) - Levy-Strumpf, Naomi
ABSTRACT: While ample information was gathered in identifying guidance cues and their downstream mediators, very little is known about how the information from multiple extracellular cues is intracellularly to generate normal patterning. Netrin and Wnt signaling pathways play key roles in normal development as well as in malignancies. In C. elegans, as in vertebrates, dorso-ventral (D/V) graded distributions of UNC-6/Netrin and antero-posterior (A/P) graded distributions of Wnts provide instructive polarity information to guide cells and axons along their respective gradients. In this commentary, I will discuss recent findings demonstrating that these 2 signaling pathways also function redundantly to regulate polarity orthogonal to the axis of their gradation. Thus, Wnt signaling components contribute to D/V polarity, while Netrin signaling components contribute to A/P polarity and their joint action collaboratively governs migratory transitions from one axis to the other. These findings pave the way to unraveling broader roles of Wnt and Netrin signaling pathways, roles that are masked due to their redundant nature, and provide a conceptually novel view of how antero-posterior and dorso-ventral guidance mechanisms are orchestrated to establish polarity in multiple biological processes.